2022
DOI: 10.3390/ph15040436
|View full text |Cite
|
Sign up to set email alerts
|

Plectranthus zeylanicus: A Rich Source of Secondary Metabolites with Antimicrobial, Disinfectant and Anti-Inflammatory Activities

Abstract: Plectranthus zeylanicus Benth is used in Sri Lankan folk medicine as a remedy for inflammatory conditions and microbial infections. Our previous investigations revealed potent 5-lipoxygenase (5-LO) inhibitory activity in lipophilic extracts of this plant, supporting its anti-inflammatory potential. In-depth studies on the antimicrobial activity have not been conducted and the bioactive ingredients remained elusive. As a continuation of our previous work, the present investigation was undertaken to evaluate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Sripathi, Jayagopal, and Ravi [47] reported an MIC value of 320 µg/mL for S. aureus and E. coli in extracts obtained by hydrodistillation. In contrast, the methanolic extracts obtained by Napagoda et al [48] showed an MIC of 500 µg/mL for S. aureus and 1000 µg/mL for Salmonella typhi. In addition, Ntungwe et al [38] reported an MIC and MBC value of 15.6 µg/mL and 250 µg/mL, respectively, for S. aureus in the ultrasound-assisted extract and Schultz et al [42] obtained an MIC of 104 µg/mL for S. aureus and an MIC of >500 µg/mL for E. coli and Listeria innocua.…”
Section: Antimicrobial Activity Of the Extractsmentioning
confidence: 76%
See 1 more Smart Citation
“…Sripathi, Jayagopal, and Ravi [47] reported an MIC value of 320 µg/mL for S. aureus and E. coli in extracts obtained by hydrodistillation. In contrast, the methanolic extracts obtained by Napagoda et al [48] showed an MIC of 500 µg/mL for S. aureus and 1000 µg/mL for Salmonella typhi. In addition, Ntungwe et al [38] reported an MIC and MBC value of 15.6 µg/mL and 250 µg/mL, respectively, for S. aureus in the ultrasound-assisted extract and Schultz et al [42] obtained an MIC of 104 µg/mL for S. aureus and an MIC of >500 µg/mL for E. coli and Listeria innocua.…”
Section: Antimicrobial Activity Of the Extractsmentioning
confidence: 76%
“…However, Kotagiri, Shaik, and Kolluru [8], as well as Sripathi and Ravi [46], reported that in addition to having antimicrobial activity against Gram-positive bacteria, PHT extracts also showed activity against Gram-negative bacteria such as Escherichia coli and Pseudomonas aeruginosa. According to Sripathi, Jayagopal, and Ravi [47], the antimicrobial activity of P. hadiensis can be attributed to the presence of monoterpenes and sesquiterpenes, mainly L-fenchone, β-farnesene, copaene, and α-caryophyllene, while Dominguez-Martín et al [10] and Napagoda et al [48] ascribe the antimicrobial activity mainly to the diterpenes 7α-acetoxy-6βhydroxyroyleanone, 7 β-acetoxy-6β-hydroxyroyleanone, and 6β,7β-dihydroxyroyleanone.…”
Section: Antimicrobial Activity Of the Extractsmentioning
confidence: 99%
“…Specifically, this compound suppresses 5-LO product formation in cell-free assays with an IC 50 of 1.3 µg/mL and in human neutrophils with an IC 50 of 5.1 µg/mL. Therefore, the inhibition of 5-LO and leukotriene production appears to be an anti-inflammatory mode of action of 7α-acetoxy-6β-hydroxyroyleanone [38]. Roy also displays immunosuppressive activity by inhibiting lymphocyte proliferation.…”
Section: Discussionmentioning
confidence: 92%
“…The current research has focused on the compound 7α-acetoxy-6β-hydroxyroyleanone (Roy) isolated from the P. grandidentatus; it belongs to the broader class of abietanes that encompasses a diverse array of plant-derived diterpenoid compounds demonstrating promising biological effects, including antibacterial, anti-inflammatory, and immunomodulatory properties, as well as cytotoxic activities in numerous cancer cell lines [35][36][37][38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…Roy displays strong antibacterial activity against methicillin-resistant Staphylococcus aureus strains with a minimum inhibitory concentration (MIC) of 62.5 µg/mL [39]. Due to its high antibacterial potency and low cytotoxicity, Roy is a promising alternative to current antibiotics for treating infections caused by resistant bacteria.…”
Section: Discussionmentioning
confidence: 99%